Pharmacotherapy for lung cancer with comorbid interstitial pneumonia: limited evidence requires appropriate evaluation. Issue 4 (12th December 2022) - Ishida, Yuriko; Ikeda, Satoshi; Sekine, Akimasa; Baba, Tomohisa; Ogura, Takashi
We have read with interest the article entitled "Lung cancer in patients with fibrosing interstitial lung diseases: an overview of current knowledge and challenges" by Kewalramani et al . [1]. ∼10% of lung cancer patients are complicated with interstitial pneumonia and have a poor prognosis. Although there is a lack of evidence in this area, the article clearly summarises the current status from epidemiology to treatment, and is very informative for clinicians. However, there were three points that could be misleading to the reader, especially in the description of pharmacotherapy. This article is a correspondence to the review article on lung cancer with comorbid interstitial pneumonia, particularly with regard to pharmacotherapy. Limited evidence needs to be accurately evaluated and utilised for these patients with poor prognosis. https://bit.ly/3BGRCz4